2021
DOI: 10.1088/1748-3190/abdd94
|View full text |Cite
|
Sign up to set email alerts
|

Dactyls and inward gripping stance for amphibious crab-like robots on sand

Abstract: Sandy beaches are areas that challenge robots of all sizes, especially smaller scale robots. Sand can hinder locomotion and waves apply hydrodynamic forces which can displace, reorient, or even invert the robot. Crab-like legs and gaits are well suited for this environment and could be used as inspiration for an improved design of robots operating in this terrain. Tapered, curved feet (similar to crab dactyl shape) paired with a distributed inward gripping method are hypothesized to enable better anchoring in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
24
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(26 citation statements)
references
References 44 publications
2
24
0
Order By: Relevance
“…The goal of our glove is to relate motions of a common hexapod leg to finger motions. A common robot leg design has three joints ( Graf et al, 2019 , 2021 ; Wooden et al, 2010 ; Boston Dynamics, 2022 ; Michael, 2012 ; Hwangbo et al, 2019 ; Darling, 2015 ; Sartoretti et al, 2018 ; Coelho et al, 2021 ), as shown in Figure 3 : a hip joint with vertical axis of rotation, a knee joint, and an ankle joint with parallel axes of rotation. Just like one robot leg has three joints, there are three joints on one finger: the metacarpophalangeal joint (MCP), the proximal interphalangeal joint (PIP) and the distal interphalangeal joint (DIP) ( Jones and Lederman, 2006 ; Palastanga and Soames, 2011 ; Wheatland et al, 2015 ).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The goal of our glove is to relate motions of a common hexapod leg to finger motions. A common robot leg design has three joints ( Graf et al, 2019 , 2021 ; Wooden et al, 2010 ; Boston Dynamics, 2022 ; Michael, 2012 ; Hwangbo et al, 2019 ; Darling, 2015 ; Sartoretti et al, 2018 ; Coelho et al, 2021 ), as shown in Figure 3 : a hip joint with vertical axis of rotation, a knee joint, and an ankle joint with parallel axes of rotation. Just like one robot leg has three joints, there are three joints on one finger: the metacarpophalangeal joint (MCP), the proximal interphalangeal joint (PIP) and the distal interphalangeal joint (DIP) ( Jones and Lederman, 2006 ; Palastanga and Soames, 2011 ; Wheatland et al, 2015 ).…”
Section: Methodsmentioning
confidence: 99%
“… Hexapod robots (left) and human hands (right) have similarities that can be convenient for user interfaces. For example, a user might want to use a single finger to lift a single leg of this crab-like hexapod ( Bjelonic et al, 2016 ; Franchi et al, 2012 ; Carpentier and Mansard, 2018 ; Grezmak et al, 2021 ; Graf et al, 2019 ; Graf et al, 2021 ). …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[ 1,2 ] There have been many other amphibious robot designs inspired by gait‐changing animals. [ 3–12 ] However, most were built of rigid components that make the interaction of the robots with the environment unwieldy. On the other hand, soft robots based on smart materials and compliant structures have displayed great potential in complying with varying terrain and unplanned situations.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, soft robots based on smart materials and compliant structures have displayed great potential in complying with varying terrain and unplanned situations. [13][14][15][16][17][18][19][20][21][22][23][24][25][26] Therefore, the development of soft amphibious robots based on different soft actuation principles was naturally carried out [4,8,[25][26][27] and was found to be successful in navigating multimodal environments. Among the different soft actuation principles explored, various soft-body movements with shape memory alloy (SMA) wires have been achieved at a compact scale, including jumping, [17] crawling, [15,28,29] peristaltic, [30,31] swimming [32] , and even rolling [14] .…”
mentioning
confidence: 99%